Building and using domain ontologies for learning in various domains: a semantic web-based learning perspective. (18th December 2008) - D'Avanzo, Ernesto; Kuflik, Tsvi; Lytras, Miltiadis D.
The deployment of semantic web in the context of learning requires a multidimensional consideration of critical issues mostly related with the integration of Semantic Web technologies into the learning context. The main purpose of this article is to discuss in depth the concept of domain ontologies and their role for the effectiveness of semantic web-based e-learning applications. The representation of the learning content and the exploitation of domain ontologies are analysed in the context of a semantic-based prototype, which will be the basis for an FP7 STREP Project proposition. The knowledge acquisition process and the continuous enrichment of the learning content base is recognised as key functions towards high learning outcomes. The main contribution of this article relates to the understanding of ontological challenges for the design and implementation of e-learning systems.